Development of an Inquiry-Based Social Complexity Science Pocketbook to Enhance Elementary Students’ Critical Thinking Skills - Khomairroh, Siti; Yulianti, Dwi; Nurwahidin, Muhammad; Adha, Mohammad Mona (Lectura : Jurnal Pendidikan, 2024)
This research problem begins with the results of a needs analysis of students. The research aims to produce a product in the form of a science pocket book based on Inquiry Social Complexity that is valid, practical and effective in order to improve students’ critical thinking skills. The type of research used Research and Development (R&D), following the ADDIE model with five stages: Analysis, Design, Development, Implementation, and Evaluation. The population of this studied consists of fifth-grade students from SD Rayon II, Sidomulyo District. The sample was determined used Cluster Random Sampling, aligned with the research objectives. Data collection tools included valid and reliable test instruments. The validation results of the Inquiry-Based Social Complexity Science pocketbook, developed by the researchers, theoretically confirmed its feasibility, with an Aiken’s V analysis yielding an average of 0.87, falling into the “Very Valid” category. Science pocket book product based on Inquiry Social Complexity which was developed to be practical in its application in the classroom. The results of the practicality assessment on educators’ responses had a holistic average score of 88.04 with a very practical interpretation and student responses had a holistic average score of 87.77 with a very practical interpretation. The data analysis technique employed an independent t-test. The calculation result was 0.009, which was less than 0.05. It is indicating a significant difference between the pre-test and post-use of the product in the class groups. This shows that the pocket book used is effective in improving students’ critical thinking skills.